(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents the results of a study of thin photoelectrophysical films of cadmium telluride (CdTe), obtained by thermal deposition on glass and molybdenum substrates using a silver dopant. The influence of substrate temperature and subsequent heat treatment on the structural, morphological, and optical properties of the films is studied. X-ray diffraction showed that the deposited films are nanocrystalline with a cubic structure, and heat treatment leads to grain growth and the formation of a polycrystalline structure. Using atomic force microscopy (AFM), the grain size and morphology of the films were determined. Optical measurements made it possible to determine the band gap, which varied from 1.45 to 1.48 eV depending on the processing temperature. CdTe-CdS photoelectrophysical elements were fabricated, for which current-voltage characteristics were obtained and the efficiency (COP) was determined to be 22%. The obtained results demonstrate the potential of using CdTe thin films in photoelectric and X-ray radiation detectors, as well as the possibility of optimizing their properties through heat treatment.